Nasal Obstruction Symptom Evaluation Score Analysis: Exploring Nasal Function in Premenopausal versus Postmenopausal Indian Women - Akhil Pratap Singh; Amit Varshney; Ruchika Garg; Prabhat Agrawal (Journal of Mid-Life Health, 2024)
Background: Menopause brings about significant hormonal changes that can affect various aspects of women’s health, including nasal function. However, the specific impact of menopause on nasal health in Indian women remains underexplored. This study aims to compare nasal function using the Nasal Obstruction Symptom Evaluation (NOSE) score between premenopausal and postmenopausal Indian women. Materials and Methods: A comparative cross-sectional study was conducted involving 107 premenopausal and 111 postmenopausal women recruited from a tertiary care hospital in India. Demographic data, medical history, and NOSE scores were collected. Statistical analyses including Wilcoxon rank-sum test, Chi-squared test, logistic regression, and receiver operating characteristic curve analysis were performed. Results: Postmenopausal women were significantly older with higher body mass index (BMI) compared to premenopausal women. Postmenopausal women consistently had higher NOSE scores indicating worse nasal function across various time points. Logistic regression revealed menopausal status as a significant predictor of severe nasal obstruction (odds ratio: 1.45, 95% confidence interval: 1.10–1.90, P = 0.015), independent of age, BMI, and other factors. Conclusion: Menopause is associated with a significant decline in nasal function in Indian women, as evidenced by higher NOSE scores in postmenopausal women. Addressing nasal symptoms in postmenopausal women may improve their quality of life. Further research is needed to develop targeted interventions for managing nasal obstruction in this population.